Kontroversi Konsep Nasikh-Mansukh dalam Tafsir Al-Qur'an: Antara Pro dan Kontra - Luthfiyah, Lujeng; Khuluq , Moh. Sahlul (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
Nasikh-mansukh is a crucial concept in the study of Qur'anic exegesis (tafsir) and has often been a subject of debate among scholars and academicians. This concept refers to verses that are believed to abrogate or alter the legal rulings contained in previous verses, making it a critical issue in understanding Islamic law. This study aims to analyze the controversy surrounding the concept of nasikh-mansukh, particularly within the context of Qur'anic exegesis, by exploring both the supporting and opposing arguments. The research employs a qualitative approach through a literature review, examining both classical and modern tafsir works that address this issue. The main findings indicate that proponents of the nasikh-mansukh concept view it as a tool to understand legal changes in the Qur'an in accordance with the social and historical context. On the other hand, critics argue that nasikh-mansukh may limit the understanding of the Qur'an's more universal message. The study concludes that acceptance or rejection of nasikh-mansukh largely depends on the interpretive approach employed by individual mufassirs. This research contributes to the enrichment of tafsir literature by offering a comparative perspective and opens up broader discussions on the relevance of nasikh-mansukh in contemporary Qur'anic exegesis.